Experimental evaluation of flat plate solar collector using nanofluids - Verma, Sujit Kumar; Tiwari, Arun Kumar; Chauhan, Durg Singh (Energy conversion and management, 2017)
•Solar collectors are special kind of heat exchangers.•Particle concentration is important parameter for thermal conductivity of nanofluid.•Rise of Bejan number indicates systems qualitative response.•Multi walled carbon nanotube is best performing. The present analysis focuses on a wide variety of nanofluids for evaluating performance of flat plate solar collector in terms of various parameters as well as in respect of energy and exergy efficiency. Also, based on our experimental findings on varying mass flow rate, the present investigation has been conducted with optimum particle volume concentration. Experiments indicate that for ∼0.75% particle volume concentration at a mass flow rate of 0.025kg/s, exergy efficiency for Multi walled carbon nanotube/water nanofluid is enhanced by 29.32% followed by 21.46%, 16.67%, 10.86%, 6.97% and 5.74%, respectively for Graphene/water, Copper Oxide water, Aluminum Oxide/water, Titanium oxide/water, and Silicon Oxide/water respectively instead of water as the base fluid. Entropy generation, which is a drawback, is also minimum in Multiwalled carbon nanotube/water nanofluids. Under the same thermophysical parameters, the maximum drop in entropy generation can be observed in Multiwalled carbon nanotube/water, which is 65.55%, followed by 57.89%, 48.32%, 36.84%, 24.49% and 10.04%, respectively for graphene/water, copper oxide/water, Aluminum/water, Titanium Oxide /water, and Silicon oxide /water instead of water as the base fluid. Rise of Bejan number towards unity emphasizes improved system performance in terms of efficient conversion of the available energy into useful functions. The highest rise in energy efficiency of a collector has been recorded in Multiwalled carbon nanotube/water, which is 23.47%, followed by 16.97%, 12.64%, 8.28%, 5.09% and 4.08%, respectively for graphene/water, Copper oxide/water, Aluminum oxide/water, Titanium oxide /water, and Silicon oxide/water instead of water as the base fluid.